2011
DOI: 10.1111/j.1440-0960.2011.00806.x
|View full text |Cite
|
Sign up to set email alerts
|

Skin disease in the first two years of life in Aboriginal children in East Arnhem Land

Abstract: Skin infections are a major reason for presentation to primary health clinics and contribute to the high disease burden experienced by children in the first 2 years of life. This high frequency of presentation provides multiple opportunities for intervention and monitoring.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
64
1
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(71 citation statements)
references
References 16 publications
4
64
1
2
Order By: Relevance
“…Limited data exists regarding prevalence of skin infection in the Kimberley and Pilbara region although other studies in regional Western and Northern Australia have found similarly high rates[5, 6, 35]. This high prevalence in our study supports our hypothesis that the under-recognition of skin infection is not a product of lack of familiarity with skin infection but rather that clinicians may ‘normalise’ skin infection because it is pervasive.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Limited data exists regarding prevalence of skin infection in the Kimberley and Pilbara region although other studies in regional Western and Northern Australia have found similarly high rates[5, 6, 35]. This high prevalence in our study supports our hypothesis that the under-recognition of skin infection is not a product of lack of familiarity with skin infection but rather that clinicians may ‘normalise’ skin infection because it is pervasive.…”
Section: Discussionsupporting
confidence: 77%
“…Similarly, scabies is very common in tropical environments particularly amongst children with population prevalence in excess of 10% in many Asian, Pacific Island and Central and South American countries[2]. Community based skin infection prevalence studies from Aboriginal populations in northern Australia demonstrate some of the highest prevalence rates of scabies and impetigo in the world[5, 6]. …”
Section: Introductionmentioning
confidence: 99%
“…The East Arnhem Regional Healthy Skin Program reported that more than 70% of children presented in 2002-2005 with scabies, almost all before they reached 2 years of age [254]. Another study of children in a remote community in the NT in 2007 found that 68% of children had presented with scabies during their first year of life, and 77% had presented in the first two years [255].…”
Section: Skin Infections and Infestationsmentioning
confidence: 99%
“…A study of a remote community in the NT in 2007 found that 82% of children presented with pyoderma in their first year of life and 87% in their first two years [255]. The pyoderma in Indigenous communities commonly involves group A streptococcus (GAS), which is responsible for continuing outbreaks of acute post-streptococcal glomerulonephritis and ARF [256,257].…”
Section: Skin Infections and Infestationsmentioning
confidence: 99%
“…W piśmiennictwie opisano liczne przykłady masowych zakażeń. Dzieci poniżej 6 lat przebyły zakażenie świerzbem: w 90% w społeczności Aborygenów w północnej Australii, w 86% w Sierra Leone, w 70% w Indiach [6,16,19], podobnie jak w domu opiekuńczym w Malezji [20]. W danych epidemiologicznych z różnych rejonów świata stwierdza się częste współistnienie świerzbu z wszawicą głowową z powikłaniami w postaci trwałej limfadenopatii.…”
unclassified